Pemanfaat Limbah Industri Furniture Sebagai Produk Kreatif Yang Memiliki Nilai Tambah Ekonomi Untuk Karang Taruna di Desa Panggung Duwet Blitar - Rosidi Azis; Moh. Ali; Sri Wahyuni; Novie Ary Priyanti (Indonesian Journal Publisher, 2023)
Utilization of furniture industry waste into creative products with added economic value is one of the efforts to improve community welfare through innovation based on local resources. This study focuses on the processing of wood waste from the furniture industry in Panggung Duwet Village, Blitar, into flower pots that have attractive designs and are in accordance with modern home decoration trends, especially those known as instagrammable. The processing process begins with sorting and cutting wood waste, followed by smoothing the surface using sandpaper, and ending with a finishing that enhances the aesthetics of the product. Innovation in flower pot design with a minimalist and natural appearance utilizing wood materials combined with natural elements, provides high appeal in the market. This study also discusses the fulfillment of production facilities in wood workshops, which include the provision of cutting, smoothing, assembly, and finishing tools, which support the efficiency of the production process. The results of the study indicate that flower pot products have great market potential, especially among ornamental plant lovers and consumers who are interested in environmentally friendly and unique home decoration products. In addition to the positive economic impact on Karang Taruna members, this program also contributes to empowering village communities through waste processing skills into high-value products. Overall, processing furniture waste into flower pots not only supports environmental sustainability but also creates new economic opportunities for village communities.